SISTEM PENDUKUNG KEPUTUSAN SISWA BERPRESTASI MENGGUNAKAN METODE WEIGHTED PRODUCT - Muhamad Muslihudin; Dewi Rahayu (Jurnal TAM (Technology Acceptance Model), 2018)
Students are people who are trying to develop themselves through the process of education on the path, level and type of education. The Weigted Product method is chosen because the method is solved by using multiplication to connect the value of the attribute, where the value must be raised with the attribute weight value in question. Criteria criteria that have been determined include: average value, discipline, attendance, extracurricular, and Non-Academic. The results of this study there are 6 alternatives, that alternative Agus with a value = 0.1618 as a student with the lowest and alternative value Diamond = 0.1748 as the student with the best value.